Keats and the Double Life of Poetry. Issue 2 (July 2016) - Cronin, Richard
Abstract : Keats, unlike the other Romantics, has prompted not just a dispute as to the character of his political allegiances, but a dispute about whether he is appropriately regarded as a political poet at all. Keats's recent critics are more familiar with the Poems of 1817 in which Keats emphatically and repeatedly identifies himself as an admiring associate of the editor of The Examiner, Leigh Hunt, but even in these poems the ambition to write a poetry that makes its impact on the non-poetic world alternates with a contrary tendency to define the world of the poem by its distance from the world outside it. In the Poems of 1820 the two tendencies persist, but, instead of working against one another, they allow Keats to resolve his contradictory ambitions and write poems that achieve a formal perfection that releases them from the contingent and yet continue to speak to the contingent world in which we all of us live our lives.